If x − y x + y = 2 , find
x y x 2 + y 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
As a side note, we have to ensure that x y = 0 , in order to justify the conclusion in the last step.
@Faiza Kashish , you should key in (x+y)/(x-y) = x − y x + y with the brackets instead of x+y/x - y = x + x y − y . Similarly (x^2+y^2)/(xy) = x y x 2 + y 2 instead of x^2+y^2/xy = x 2 + x y 2 y . Better still you use LaTex. You can see the LaTex codes by clicking on the pull-down menu ( ⋯ ) at the right-hand-bottom corner of the problem and select "Toggle LaTex".
OK I will take care@chew seong cheong sir
Simply apply C-D Rule and break the given expression
First of all, note that;
If
x
=
0
or
y
=
0
;
Then,
x
−
y
x
+
y
will be
−
1
and
1
respectively; So, we can safely conclude that
x
y
=
0
; hence the required fraction is NOT indeterminate for any value of the variables.
Now,
Let
x
y
x
2
+
y
2
=
a
;
⟹
x
2
+
y
2
−
2
x
y
x
2
+
y
2
+
2
x
y
=
a
−
2
a
+
2
;
⟹
(
x
−
y
)
2
(
x
+
y
)
2
=
a
−
2
a
+
2
;
⟹
2
=
a
−
2
a
+
2
;
⟹
2
a
−
4
=
a
+
2
;
⟹
a
=
6
Note that componendo et dividendo was used in 2nd step and value of x − 2 x + 2 was put as 2 in 4th step and other steps follow.
Nice usage of componendo and dividendo !
A = x − y x + y = 2
x + y = 2 x − 2 y
x + y = 2 x − 2 y
( 2 + 1 ) y = ( 2 − 1 ) x
It is easy to see, that in the case of x=y=0, A would be undefined (division by zero); and in the cases ( x = 0 and y ≠ 0) or ( x ≠ 0 and y = 0), A = 1 would be true (instead of the A = square root of 2)).
Therefore, x≠ 0 and y ≠ 0 and we can divide by both x and y.
Now:
y x = 2 − 1 2 + 1 = 2 − 1 2 + 1 × 2 + 1 2 + 1 = 2 − 1 2 + 2 2 + 1 = 3 + 2 2
Similarly:
x y = 2 + 1 2 − 1 = 2 + 1 2 − 1 × 2 − 1 2 − 1 = 2 − 1 2 − 2 2 + 1 = 3 − 2 2
Then:
B = x y x 2 + y 2 = x y x 2 + x y y 2 = y x + x y = 3 + 2 2 + 3 − 2 2 = 6
we actually need to find y x + x y from given data by dividing in numerator and denominator by y and substiting value of y x .
First of all note that the condition for either of x or y to be zero is non-existent since, x − y x + y = 2 for any value of the other non-zero variable if x y = 0 .
So, proceeding by the hint as stated in the title of the problem, divide both the numerator and denominator of the LHS of the equation by y to get,
y x − 1 y x + 1 = 2
Similarly for the expression to be obtained, one can write it as,
y x ( y x ) 2 + 1 Dividing numerator and denominator by y 2
Take y x as a separate variable, z ,and solve accordingly,
⟹ z − 1 z + 1 = 2 z = 2 − 1 2 + 1 = 3 + 2 2
Plugging in z in our required expression, we get,
3 + 2 2 ( 3 + 2 2 ) 2 + 1 = 6
Problem Loading...
Note Loading...
Set Loading...
x − y x + y x + y ( x + y ) 2 x 2 + 2 x y + y 2 2 x y x 2 + y 2 ⟹ x y x 2 + y 2 = 2 = 2 ( x − y ) = 2 ( x − y ) 2 = 2 x 2 − 4 x y + 2 y 2 = x 2 − 4 x y + y 2 = 6 x y = x y 6 x y = 6 for x y = 0